The Battery-Driven Electromagnetic Flow Converter with Reduced Power Consumption - Katutis, R.; Vaikasas, R.; Virbalis, J. A. (Elektronika ir Elektrotechnika, 2010)
Power used for magnetic field excitation can be minimized by applying a capacitor and the oscillating character of the transient process. Pulses of the excitation current are the half-periods of the sinusoid in this case. We obtain the more effective suppression of the transform component integrating the electrode signal in the sine phase intervals [π/6, 5π/6] and [π+π/6, π+5π/6]. The quantitative evaluation of the power consumption reduction is obtained in respect to ratio between critical and active resistances of the excitation circuit. The power consumption which arises because the capacitor discharge between neighbouring current pulse is negligible. Ill. 5, bibl. 2 (in English; abstracts in English, Russian and Lithuanian).